(untitled) (2021)
It is intended to determine the economic and financial potential of cocoa cultivation in the Santander department, under the methodology of evaluation of agricultural projects, to measure benefits associated with financial profitability factors, benefit-to-cost ratio and sensitivity analysis, on variables that producers do not normally estimate, either out of knowledge or because they do not give importance, allowing you to make better decisions. To this end, cocoa bean yields are characterized, based on production information and establishment costs per hectare between 2012 and 2016; revenue, other input expenditures and tools projected at 25 years as an evaluation horizon are also estimated to allow the respective statistical simulations to be carried out to determine key variables for decision-making. The results show that the crop is profitable, because the simulation yields a maximum NPV of $20,504,270, an IRR greater than 19% and a Cost-Benefit Analysis of 1.27, therefore it is concluded that there isfinancial profitability; however, particular attention should be paid to the quantities produced, sales prices and inputs, as these variables have a high level of sensitivity to expected changes.